Sekai no Owari dan Shuhasu: Kajian Semiotika Riffaterre - Budi Mustapa Husin Sagala; I Wayan Wahyu Cipta Widiastika (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2024)
Abstract This article analyzes and describes the indirect meaning of the song